Manajemen Pendidikan dalam Perspektif Islam - Madarik, Muhammad (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2025)
The basic principles of management can be narrowed down to four things: [1] people; [2] resources; [3] goals; and [4] time. When these four elements are realized, they appear as a social unit called an "organization". It can be concluded that management work is a subsystem of the organization. Management is the key to organizational success because with effective management, organizations can achieve goals efficiently. Management in the Qur'an is not clearly stated. But the function or purpose in the conceptual approach of the Qur'an as values will be found to be much relevant. These values include: [1] Management as an individual and collective responsibility (QS. 99:7-8). [2] Management as a means of dividing work (QS. 06:165). [3] Management as work that must be accounted for (QS. 52:21 and QS. 74:38). [4] Management as a way of efficient and productive financial management (QS. 25:67). [5] Management as planning and foresight (QS. 59:18). The dynamics of thought on Islam and education are mapped: [1] The radical and scripturalist “universalist” group. Its figures are: Sheikh Hasan al-Banna, Sayyid Qutb, Sheikh Muhammad Rasyid Ridla, and Maulana Abul A’la al-Maududi. Their argument: Islam regulates the way of life from the smallest to the largest problems, including the education system. [2] The group influenced by western liberalism. Its figures are: Ali Abd al-Razik and Thaha Husein. Their argument: There is no Islamic education but Islamic education. [3] The group that tends to be liberal. Its figures include Husein Haikal. Their argument: Education is an area of creative thinking (ijtihadi) on the foundation of Islamic values.